Analysis of the Societal Benefits Derived from Reducing Pharmaceutical Prices based on System Dynamics - Zhang, Yuzhu; Cheng, Yunxia; Guo, Yiting; Hu, Rong; He, Qiang (Transactions on Economics, Business and Management Research, 2024)
The steep prices of pharmaceuticals have long been a significant concern in the healthcare domain, directly impacting patients' financial burdens, government healthcare expenditures, and the operational dynamics of the pharmaceutical market. This study aims to analyze the societal ramifications of lowering drug prices through the lens of system dynamics methodology. Employing a system dynamics model, this study evaluates the effects of drug price adjustments on patients, governments, and the broader society, while also investigating the outcomes across various policy and market scenarios. Findings indicate that reducing drug prices within a certain range can alleviate patients' financial burdens, enhance the accessibility and equity of healthcare services, and decrease government healthcare expenditures, thereby bolstering healthcare coverage. Additionally, the decline in drug prices contributes to narrowing the wealth gap and fostering social equity and stability. The outcomes of this study offer valuable insights for government policy-making and market management in the pharmaceutical sector, facilitating the advancement of a robust pharmaceutical market and societal progress.